Ecohydrological analysis of Steelhead (Oncorhynchus mykiss) habitat in an effluent dependent stream in the Pacific Northwest, USA. Issue 2 (20th March 2013) - Sánchez‐Murillo, R.; Brooks, E.S.; Sampson, L.; Boll, J.; Wilhelm, F.
ABSTRACT A conundrum exists in the US Pacific Northwest (PNW) whereby increasingly stringent federal environmental regulations governing the discharge of nutrients from wastewater treatment plants (WWTP) to low order streams may negatively impact salmonid species listed under the US Endangered Species Act (ESA). We examined baseflow, water chemistry, benthic algal biomass, macroinvertebrate diversity, and steelhead in the West Fork Little Bear Creek (WFLBC), Idaho, USA, above and below the city of Troy WWTP to explain why this creek is the most productive juvenile steelhead stream in the Potlatch River drainage. Discharge from the WWTP maintained 6 km of perennial flow during summer. Dissolved oxygen (DO) levels indicate that nitrification depressed DO below the Idaho state standard of 6 mg/L within the first 200 m downstream of the discharge. Because of rapid re‐aeration, DO concentrations recovered by 1.3 km. Despite high nitrate (0.12 – 4.3 mg/L) and total phosphorus (0.11 – 0.60 mg/L) concentrations 2.5 km downstream, benthic algal biomass remained below the US Environmental Protection Agency's 'nuisance algae' level (i.e., 150 mg/m2) throughout the stream. Family biotic index indicated good water quality conditions above and 2.5 km downstream of the discharge, although fairly poor condictions were found 200 m downstream from the effluent. The WFLBC ecosystem appears to have the capacity to accept and actually benefit from high nutrient loads from a WWTP. This work emphasizes the importance of developing a thorough understanding of the site‐specific biochemical functioning of an ecosystem before selecting and applying standard management practices. Copyright © 2013 John Wiley & Sons, Ltd.